Seasonal and public holiday effects in the commercial rand/dollar exchange rate during the period 1984-1995 - D. N. Greshnev; E. V.D.M. Smit (South African Journal of Business Management, 1997)
The aim of the research is to extend the existing research into seasonalities in financial markets to the South African foreign exchange market to determine whether any of the known seasonal patterns are present in daily changes in the commercial S.A. rand/U.S. dollar exchange rate over the 11-year period, 1984 to 1995. Only statistically significant seasonal patterns in findings in the exchange rate changes for January versus other non-turn-of-the-month days effect are demonstrated. Contrary to the findings for the the mean daily changes, the volatility of the exchange rate demonstrates persistent and statistically significant seasonal anomalies for nearly all of the examined seasonal effects. A number of popular theories offering explanation of the seasonal regularities in the financial markets are offered as possible explanations for the findings.
Keywords: 650